2018
DOI: 10.1016/j.echo.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Left Ventricular Rotational Mechanics in Children with Noncompaction Cardiomyopathy: Do They Influence Ventricular Function?

Abstract: RAR is not a sensitive but is a specific indicator of complications in children with NCC. Therefore, RAR may have prognostic rather than diagnostic value. Premature untwisting of the left ventricle during ejection may be an even more worrisome indicator of LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Bellavia et al reported that in adults, the value of LV rotation/torsion excessively decreased in patients with LVNC, whereas normal EF were retained when compared with those in controls [31]. Nawaytow et al reported that almost half of the children with LVNC exhibit reverse apical rotation, resulting in decreased LV torsion and untwist rate, which are associated with the degree of LVNC [34]. These previous studies might support that the deterioration of LV function occurs during the perioperative period, although LV systolic function was preserved preoperatively because of its unique structure.…”
Section: Discussionmentioning
confidence: 99%
“…Bellavia et al reported that in adults, the value of LV rotation/torsion excessively decreased in patients with LVNC, whereas normal EF were retained when compared with those in controls [31]. Nawaytow et al reported that almost half of the children with LVNC exhibit reverse apical rotation, resulting in decreased LV torsion and untwist rate, which are associated with the degree of LVNC [34]. These previous studies might support that the deterioration of LV function occurs during the perioperative period, although LV systolic function was preserved preoperatively because of its unique structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that patients with LVNC< 2 accounted for about half of the patient group in this research. Some researchers have suggested that technological advances in image resolution have led to a more intricate visualization of the left ventricular myocardium, resulting in overdiagnosis of LVNC [26]. The important question posed by this study was whether the high proportion of patients fulfilling the current diagnostic criteria for LVNC with an NC/C ratio < 2 was explained by a genuine congenital abnormality or an exaggeration of the normal trabeculation patterns.…”
Section: Discussionmentioning
confidence: 87%
“…Ratio of LV-RBR was significantly different between NCCM children and subjects with hypertrabecularization [19]. In another study, reverse LV apical rotation (Cw LV-RBR) was present in 39% of NCCM children [20].…”
Section: Noncompaction Cardiomyopathymentioning
confidence: 90%
“…Specificity and sensitivity of LV-RBR was 88% and 78% in differentiating NCCM from LV "hypertrabeculation", respectively [12]. Cw LV-RBR was detected in most NCCM cases [11,12,15,[18][19][20], which was found to be related to LV-EF [17]. Almost one-third of the relatives of NCCM patients showed LV-RBR, the ratio of Cw and CCw direction was the same [18].…”
Section: Noncompaction Cardiomyopathymentioning
confidence: 90%
See 1 more Smart Citation